2014
DOI: 10.1016/j.ijcard.2014.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Sleep apnea prevalence in acute myocardial infarction — The Sleep Apnea in Post-acute Myocardial Infarction Patients (SAPAMI) Study

Abstract: Background While sleep apnea (SA) might be a modifiable cardiovascular risk factor, recent data suggest that SA is severely underdiagnosed in patients after acute myocardial infarction (MI). There is limited evidence about day-night variation of onset of MI on dependence of having SA. We therefore investigated the prevalence of SA and examined the day-night variation of onset of MI in acute MI patients. Methods We prospectively studied 782 consecutive patients admitted to the hospital with the diagnosis of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
19
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 32 publications
2
19
1
1
Order By: Relevance
“…Ben Ahmend et al (22) reported a 79% prevalence of OSAHS with AMI for 120 people in France. Ludka et al (10) reported a 65.7% prevalence in Brno, Czech Republic. In comparison with the prevalence of SAHS in CAD (approximately 60%), that in AMI undergoing emergency pPCI is much higher.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Ben Ahmend et al (22) reported a 79% prevalence of OSAHS with AMI for 120 people in France. Ludka et al (10) reported a 65.7% prevalence in Brno, Czech Republic. In comparison with the prevalence of SAHS in CAD (approximately 60%), that in AMI undergoing emergency pPCI is much higher.…”
Section: Discussionmentioning
confidence: 96%
“…Findings from published reports present that the prevalence of SAHS among patients with AMI is up to 60% (10), which is mostly ignored by physicians on the cardiac intensive care unit (CCU), not to mention treatment. Some studies about the effect of SAHS on AMI showed that SAHS would worsen the condition in patients with AMI.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we used the overall apnea-hypopnea index, without specific subanalysis for obstructive and central events. Indeed, we specifically note the inability to discriminate between obstructive and central events as a significant limitation of our study [1].…”
mentioning
confidence: 94%
“…We thank Dr. Kuwada for the comments related to our study [1] and are pleased to provide specific answers below.…”
mentioning
confidence: 99%
“…To the Editor: I read the study by Ludka et al with interest [1]. The authors investigated the prevalence of sleep apnea (SA) and examined the daynight variation of onset of myocardial infarction (MI) in 607 acute MI patients.…”
mentioning
confidence: 99%